How do we know - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
How do you know what you know - and why? While science is often considered the most reliable road to the truth, is there a limit to what science can explain? Should we trust scientific knowledge, more than we trust the knowledge drawn from other disciplines such as religion, spirituality, philosophy and history?
Executive producer, Nasuhi yurt.
Host : MaryLynn Schiavi
Keywords: Science